Effect of variabilities on mechanical properties of textile composites - Matveev, Mikhail Y. (2015)
This work explores effects of selected sources of variability on mechanical properties of textile composites. Current modelling approaches rely on an idealised representation of the geometry and properties of composites while in reality the properties are not uniform and the structure has local variations. Existing approaches to model these variations showed that they can affect manufacturing processes for textile composites and compressive strength of unidirectional composites. This work is an attempt to extend existing methods for modelling of idealised composites and combine them with stochastic approaches in order to predict variability of strength and Young’s modulus of textile composites.